Enhanced wound healing effect of Areca catechu L. ointment via antibacterial activity and anti-inflammatory process at grade IIA burns in rats - Ni Made Dwi Sandhiutami; Fahleni Fahleni; Nur Miftahurrohmah; Ni Kadek Ari Widhiyasari; Afifah Azalia; Indah Amalia (Journal of HerbMed Pharmacology, 2023)
Introduction: Areca catechu L. seeds contain flavonoids, tannins, saponins, and alkaloids that have antibacterial properties, can prevent skin infections, and have been used empirically for wound healing. This study aimed to determine the antibacterial activity and effectiveness of A. catechu ointment in wound healing at grade IIA burns in rats. Methods: A. catechu seed extract was formulated into an ointment and then tested for its antibacterial activity using the agar diffusion method. Wound healing testing was conducted by dividing the rats into four groups: negative control, positive control, Formula I (F 1) ointment, and Formula II (F II) ointment. Grade IIA burns were made on the back skin of rats and treatment was performed for 14 days. The wound tissue was taken for histopathological observations. Results: In this study, F II ointment had better antibacterial activity than F I, as indicated by a wider diameter of inhibition against bacteria Pseudomonas aeruginosa, Acinetobacter baumannii, Escherichia coli, Streptococcus pyogenes, and Staphylococcus aureus. The scab formed on F II was faster on day 3, the wound diameter was reduced on day 7, and there was a decrease in inflammatory cell infiltration and coagulative necrosis and an increase in neovascularization and collagen formation on the 7th day (P < 0.05) compared to the negative control and F I. Conclusion: A. catechu seed extract ointment with a concentration of 5.0% (F II) had a better effect on wound healing regarding the antibacterial and anti-inflammatory activity than that with a concentration of 2.5% (F I).